Manfaat Film Nussa dan Rara sebagai Media Pendidikan Karakter pada Siswa Kelas II Sekolah Dasar - Septarianti, Septarianti; Susilawati, Susilawati; Ridwan, Ita Rustiati (Didaktika, 2021)
Character education of children is important in relation to children. This is very influential on the nation because it forms the nation's character from an early age. This is because children at this age are very important for character formation. Therefore, it is necessary to provide appropriate educational media that can shape the character of students for the better. The educational media uses educational television shows such as the films Nussa dan Rara. This study aims to determine the benefits contained in the film Nussa dan Rara and to find out how to grow character in second-grade elementary school children in teaching and learning activities through the delivery of the film. In this study, the researcher only took three episodes, namely Tolong dan Terima Kasih (Please and Thank You) episode, Berani Jujur (Dare to be Honest) episode, and Jangan Sombong (Don't Be Arrogant) episode. This type of research is qualitative using case study methods and using auxiliary instruments, namely interview sheets, questionnaires, and documentation. Then the results of this study are expected to contribute to character education and become input for students, teachers, other researchers, and any party in need.